Spatial Distribution for Corn Root Worm Diabrotica speciosa (Coleoptera: Chrysomelidae) on Maize Crops (Research, Society and Development, 2025)
To develop a sequential sampling plan based on the guidelines of Integrated Pest Management (IPM), it is important to know the spatial distribution of the pest in question. The corn rootworm Diabrotica speciosa (Germar) (Coleoptera: Chrysomelidae) is a significant pest in the field corn (Zea mays L.) Brazil. The objective of the present study was to collect data on the distribution model of the adults of D. speciosa in the Bt and non-Bt maizefields. Samples were collected in six field trials of 250 m2 each, during 2012 and 2013. Each field was divided into 100 plots, each measuring 25m2 (5 ×5m) in area. The sampling unit for all the samples involved five randomly selected plants that were tested in each plot, a total 500 of plants per field. The number of adults of D. speciosa, was counted weekly, for a total of between five and seven samples per field. The dispersion index (variance / mean; Morisita index and the exponent of the negative binomial K) and chi-square fit of the values observed and expected for the theoretical frequency distribution (Poisson, negative binomial and binomial positive), showed that regardless of the cultivar, the adults of D. speciosa showed an aggregated distribution pattern, adjusting to the negative binomial model.